2018
DOI: 10.14744/anatoljcardiol.2018.35902
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs expression profile of persistant atrial fibrillation in patient with rheumatic heart disease

Abstract: Objective: To investigate the expression profile of circular RNAs (circRNAs) and proposed circRNA–microRNA (miRNA) regulatory network in atrial fibrillation (AF). Methods: Atrial tissues from patients with persistent AF with rheumatic heart disease and non-AF myocardium with normal hearts were collected for circRNA differential expression analyses by high-throughput sequencing. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…MicroRNA is a hot topic in the field of cardiovascular research in recent years [ 7–9 ]. Nevertheless, there are few reports of microRNA in the research of RHD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA is a hot topic in the field of cardiovascular research in recent years [ 7–9 ]. Nevertheless, there are few reports of microRNA in the research of RHD [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hu M et al established circRNA expression profiles of persistent atrial fibrillation(AF) in cases carrying rheumatic heart disease. Circ_19591, circ_ 19596 and circ_16175 showed interactions to 36, 28, and 18 miRNAs, respectively; miR-29b-1-5p and miR-29b-2-5p displayed associations with 12 reduced circRNAs, respectively, which proposes an emerging perspective on circRNAs that participate part in AF for rheumatic heart disease and then lays a foundation for subsequent studies on the probable effects of circRNAs on AF [75].…”
Section: Circrnas In Viral and Bacterial Infectionsmentioning
confidence: 86%
“…In addition, by studying the circRNA expression profiles in atrial tissues from patients with persistent atrial fibrillation (AF) with rheumatic heart disease, Hu et al 104 predicted the potential roles of the differentially expressed circRNAs. The results suggested that 51 circRNAs were upregulated, and 57 circRNAs were downregulated in AF tissues compared with controls, respectively.…”
Section: Circrnas In Autoimmune Diseasesmentioning
confidence: 99%